2016
DOI: 10.1016/j.acra.2016.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Flipping Radiology Education Right Side Up

Abstract: Flipped learning was associated with increased academic achievement, greater task value, and more positive achievement emotions when compared to traditional didactic instruction. Further investigation of flipped learning methods in radiology education is needed to determine whether flipped learning improves long-term retention of knowledge, academic success, and patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(114 citation statements)
references
References 39 publications
5
98
0
11
Order By: Relevance
“…120 articles were taken forward for abstract review, 94 articles were excluded (see figure 1). The remaining 26 articles went forward to full text review, of which 15 were excluded (nine failed to compare FC and DT, five provided inadequate objective test results, one using Chinese medicine) leaving eleven studies (Belfi, Bartolotta, Giambrone, Davi, & Min, 2017;Bonnes et al, 2017;Boysen-osborn et al, 2016;Connor et al, 2016;Evans et al, 2016;Gillispie, 2016;Heitz, Prusakowski, Willis, & Franck, 2015;Liebert et al, 2017;Morton & Colbert-getz, 2016;Rui et al, 2017) which were included in quantitative analysis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…120 articles were taken forward for abstract review, 94 articles were excluded (see figure 1). The remaining 26 articles went forward to full text review, of which 15 were excluded (nine failed to compare FC and DT, five provided inadequate objective test results, one using Chinese medicine) leaving eleven studies (Belfi, Bartolotta, Giambrone, Davi, & Min, 2017;Bonnes et al, 2017;Boysen-osborn et al, 2016;Connor et al, 2016;Evans et al, 2016;Gillispie, 2016;Heitz, Prusakowski, Willis, & Franck, 2015;Liebert et al, 2017;Morton & Colbert-getz, 2016;Rui et al, 2017) which were included in quantitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Four of the five studies demonstrated a clear, statistically significant, improvement in assessment scores for the FC groups over the DT (Belfi et al, 2017;Bonnes et al, 2017;Connor et al, 2016;Rui et al, 2017) with one study demonstrating no improvement for FC over DT (Heitz et al, 2015). Two of the studies used a crossover design with students experiencing both DT and FC conditions in an emergency medicine clerkship and radiology clerkship (Connor et al, 2016;Heitz et al, 2015). These studies shared similar designs with two groups of students experiencing four modules, two of which were FC and two DT.…”
Section: Test Scoresmentioning
confidence: 88%
See 3 more Smart Citations